Draft genome sequences of five Calonectria species from Eucalyptus plantations in China, Celoporthe dispersa, Sporothrix phasma and Alectoria sarmentosa - Feifei Liu; Shuaifei Chen; Maria A. Ferreira; Runlei Chang; Mohammad Sayari; Aquillah M. Kanzi; Brenda D. Wingfield; Michael J. Wingfield; David Pizarro; Ana Crespo; Pradeep K. Divakar; Z. Wilhelm de Beer; et al. (IMA Fungus)
Abstract Draft genome sequences of five Calonectria species [including Calonectria aciculata, C. crousiana, C. fujianensis, C. honghensis and C. pseudoturangicola], Celoporthe dispersa, Sporothrix phasma and Alectoria sarmentosa are presented. Species of Calonectria are the causal agents of Eucalyptus leaf blight disease, threatening the growth and sustainability of Eucalyptus plantations in China. Celoporthe dispersa is the causal agent of stem canker in native Syzygium cordatum and exotic Tibouchina granulosa in South Africa. Sporothrix phasma was first discovered in the infructescences of Protea laurifolia and Protea neriifolia in South Africa. Alectoria sarmentosa is fruticose lichen belongs to the alectorioid clade of the family Parmeliaceae. The availability of these genome sequences will facilitate future studies on the systematics, population genetics, and genomics of these fungi.